STUDENTS' MOTIVATION LEARNING ENGLISH FOREIGN LANGUAGE (EFL) AT JUNIOR HIGH SCHOOL - Hidayah, Tiffany Nur; Pambayun, Rizki Nurfida; Novitasari, Devi (Esteem Journal of English Education Study Programme, 2025)
This study aims to explore the motivation of junior high school students in learning English as a Foreign Language (EFL). The participants in this research were 20 seventh-grade students from a junior high school in Banyuwangi. A descriptive qualitative approach was used for the study. Data were collected through questionnaires and interviews. The analysis of the data revealed that each student exhibited different levels of motivation towards learning EFL. The findings indicate that the students showed motivation in both their ability and attitude toward learning English, with overall positive motivation toward learning the language.